2020
DOI: 10.1152/ajpcell.00445.2019
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ precursors protect corneal endothelial cells from UVB-induced apoptosis

Abstract: Excessive exposure of the eye to ultraviolet B light (UVB) leads to corneal edema and opacification because of the apoptosis of the corneal endothelium. Our previous study found that nicotinamide (NIC), the precursor of nicotinamide adenine dinucleotide (NAD), could inhibit the endothelial-mesenchymal transition and accelerate healing the wound to the corneal endothelium in the rabbit. Here we hypothesize that NIC may possess the capacity to protect the cornea from UVB-induced endothelial apoptosis. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…NMN had been reported to be related with the incidence of a variety of chronic diseases 17 and recently reported to play a protective effect in ocular diseases. 16 In the present study, it was confirmed HS treatment would lead to an increased expression of IL-17a in CEC and thus induce the activation of macrophage based on a CEC/ macrophage co-culture system. Moreover, NMN could significantly alleviate HS-induced IL-17a secretion and moderate the subsequent macrophage activation through Notch pathway.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…NMN had been reported to be related with the incidence of a variety of chronic diseases 17 and recently reported to play a protective effect in ocular diseases. 16 In the present study, it was confirmed HS treatment would lead to an increased expression of IL-17a in CEC and thus induce the activation of macrophage based on a CEC/ macrophage co-culture system. Moreover, NMN could significantly alleviate HS-induced IL-17a secretion and moderate the subsequent macrophage activation through Notch pathway.…”
Section: Discussionsupporting
confidence: 68%
“…15 Besides, local supplementation of NMN can effectively prevent corneal endothelial cell apoptosis from UVB exposure by reactivating AKT signaling. 16 To detect the effects of NMN on the CECmacrophage interaction in the development of DED, we conduct an in-vitro study and the aims of this study included (1) detection of the protective effects of NMN on HS-induced CEC and (2) clarification of the effects of IL-17a on biological functions of macrophage. in 37°C in a 5% CO 2 atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to UVB (290-320 nm) could result in histologic and clinical injuries such as skin aging, skin inflammation, infection and cancers (Wang et al, 2019). Some reports indicate that both NMN and lactic acid bacteria have a variety of biological activities and have a photoprotective effect on the skin damaged by UVB (Kim et al, 2019a;Zhao et al, 2020). However, there are few reports on exploring the improvement effect of the combination of these two substances on UVB-induced skin damage.…”
Section: Discussionmentioning
confidence: 99%
“…The supplement of NMN restored the activation levels of SIRT1, AKT, and CREB, and reversed the cell apoptosis and epithelial defects . A recent study also reported that subconjunctival injection of NMN or other NAD+ precursors effectively prevented ultraviolet B light (UVB)induced tissue damage and EC apoptosis in the mouse cornea through reactivating AKT signaling (Zhao et al, 2020). These findings demonstrate that NMN could be a therapeutic agent for treating diverse diseases that are associated with blindness.…”
Section: Retinal Degeneration and Corneal Injurymentioning
confidence: 82%